Adab Murid Dan Guru Perspektif Ibnu Jamā’ah Dalam Kitab Tazkirah As-Sami’ Wa Al-Mutakallim - Syiehd Achmed Farhan; Fajar Syarif; Muh. Ubaidillah Al Ghifary (Mathematics Education Study Program, 2025)
The problem in this journal is that the decadence of manners between teachers and students has begun to erode in this era and the need to reactualise manners education in Indonesia. The purpose of this journal is to describe the internal and external manners of students and teachers in the study of the book of Tazas-Sa>mi' wa Al-Mutakallim. The results of this study indicate that 1). the internal adab of students in the book of Tazconsists of eleven points, namely: having the nature of wara', qana'ah, maintaining the manners of walking, maintaining the manners of sitting and others. The external manners of students in the book consist of four points, namely: obeying his teacher, honouring him, being patient with him, speaking kindly to him. 2). The internal manners of the teacher in the book consist of eleven points, namely: having zuhud, muraqabah, sincerity, noble character and others. The external manners of the teacher in the book consist of nine points, namely: not refusing to learn, not prolonging the lesson, being objective, not burdening the student and others. 3). The manners that need to be considered for students to overcome and minimise the decadence of manners, namely: Sincere intention, not underestimating the teacher, thanking him, and others. As for the teacher: maintain his authority, have noble character, do not answer when students talk to him, and others.